1977
DOI: 10.1148/124.3.641
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cholografin and Renografin 76 on Platelet Function

Abstract: Cholografin and Renografin 76 were studied to determine their effects on platelet function. In vitro platelet aggregation was significantly inhibited by at least 3.4 micron/ml Cholografin and 19.5 micron/ml Renografin 76. Patients who received Cholografin for intravenous cholangiography, and Renografin 76 for non-cardiac angiography, had low levels of plasma contrast agent, and hemostasis was clinically unimpaired. Patients who received Renografin 76 for cardiac angiography had inhibition of platelet aggregati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

1979
1979
1991
1991

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…(23), SHAPIRO et coll. (18) and COGAN et coll, (4) using aggregometers, whereas FRITZLER et coIl. (5) found platelet aggregation by electron microscopy.…”
Section: Discussionmentioning
confidence: 99%
“…(23), SHAPIRO et coll. (18) and COGAN et coll, (4) using aggregometers, whereas FRITZLER et coIl. (5) found platelet aggregation by electron microscopy.…”
Section: Discussionmentioning
confidence: 99%
“…[ l ] However, there are several reports of inhibition by contrast agents of platelet aggregation, [3-111 while Verdirame et al [12] and Shapiro et al [13] found no effects.…”
Section: Introductionmentioning
confidence: 99%
“…Platelet function expressed as the contact activation has been reported to be little affected by Renografin 60 ex vivo [7]. Another report showed that Cholografin and Renografin 76 had significant platelet inhibitory effects in vitro [8], but the author noted the in vivo inhibitory effect only at high levels of plasma contrast agents. In a recent experimental study, Motomiya et al [9] found that rabbits that received 10 ml of Urografin 76 demonstrated a transient decrease in platelet aggregation for at least 3 min.…”
Section: Discussionmentioning
confidence: 99%